(untitled) (Comillas Journal of International Relations, 2018)
In a moment where credibility and citizen support towards international organisations are suffering, it is necessary that these organisations make efforts in communicating the importance they have in the lives of the citizens as well as the achievements their actions represent in both the national and international levels. Some examples of the citizen disaffection are the rise or even the victory of parties and candidacies that challenge the benefits and the importance or organisations like the UN or the European Union. Trump, the brexit or the fact that Marine Le Pen made it to the second round of the French presidential elections, make it clear that there is a hostile environment for multilateralism. Communication must represent a key element for achieving the objective of showing the benefits and usefulness of international organisations. Therefore, we will analyse the current communication strategies of the UN and the EU in order to highlight the positive and improvable aspects of such strategies. The objective of this study is to focus on the constructivist approach of international organisations, where the management of intangible assets is key in order to change norms at the service of the common good. For that, it is vital to use soft power, which has communication as a key tool. Today, there are mechanisms that enable the direct interaction with the citizens, so a good investment in this sense can generate very positive results that return credibility to international institutions.